Penerapan Bahasa Jurnalistik Pada Kategori Berita Hukum dan Kriminal di Media Online Radar Bandung - Fatimah, Siti; Fanaqi, Chotijah; Erfan, Muhammad (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
News coverage in the legal and criminal categories has a significant potential to shape public opinion and influence percepcions of both perpetrators and victim. Therefore, the use proper journalistic language is crucial to ensure that the information conveyed remains accurate, neutral, and not misleading. This study aims to explain the application of journalistic language in legal and criminal news articles published by the online media Radar Bandung from October 1 to 22, 2024. The main issue addressed is the extent to which the media applies journalistic language principles that are simple, effective, and easy to understand, in line with the Social Responsibility Theory of the Press. The research employs a desciptive qualitative approach using observation, interviews, documentation, and literature study techniques. The findings show that, technically, Radar Bandung has applied the inverted pyramid structure and the 5W+1H elemens. However, the use of emotional, idiomatic, and potentially misleading diction was found, such as the words “bogem”(punch) and “bikin geleng-geleng” (makes one shake their head). Additionally, not all articles fulfill the principles of balance and the presumption of innocence. In conclusion, Radar Bandung, needs to strengthen its editorial guidelines and provide ethical journalism training to maintain neutrality and accuracy in legal and criminal news reporting.